Word Embeddings trained on English Wikipedia - Språkbanken Text (University of Gothenburg, 2024)
See See https://zenodo.org/record/6542975

See See https://zenodo.org/record/6542975
Engelska inbäddningar (word embeddings)
Keywords: Language Technology (Computational Linguistics); model; Natural Language Processing; Språkbehandling och datorlingvistik